2017
DOI: 10.1186/s13690-017-0224-6
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis on child mortality and its determinants in Bangladesh using frailty models

Abstract: BackgroundBangladesh has experienced a significant reduction of child mortality over the past decades which helped achieve the Millennium Development Goal 4 (MDG 4) target. But the mortality among under-5 aged children is still relatively high and it needs a substantial effort to achieve the Sustainable Development Goal (SDG) target and decelerate the current rate of under-5 mortality. At this stage, it is hence important to explore the trend and determinants of under-5 mortality in order to reduce the vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
74
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 45 publications
21
74
3
Order By: Relevance
“…Our results also suggested that the burden of low birth weight in Bangladesh reduced significantly over the last decade – from 30% in 1998 to 20% in 2014 [14]. This reduction in low birth weight has also contributed to reduction of infant mortality in Bangladesh [15].…”
Section: Discussionsupporting
confidence: 62%
“…Our results also suggested that the burden of low birth weight in Bangladesh reduced significantly over the last decade – from 30% in 1998 to 20% in 2014 [14]. This reduction in low birth weight has also contributed to reduction of infant mortality in Bangladesh [15].…”
Section: Discussionsupporting
confidence: 62%
“…A previous study conducted using the EDHS 2011 [22] suggested that multiple births were more likely to die than singletons. Another study conducted in southwest Ethiopia [23] also suggested that twins, were much more likely to die than single births, even after taking their birth weight into account.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a few studies have assessed the determinants of child mortality in Bangladesh6 7 but none of these studies considered to measure the association between maternal height and risk of mortality among neonates, infants and under-five children in Bangladesh. Therefore, in this study, we examined the association of maternal height with neonatal, infant and under-five mortality adjusting for other maternal, child and socio-demographic covariates using a nationally representative sample.…”
Section: Introductionmentioning
confidence: 99%